2014
DOI: 10.1016/j.jglr.2014.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Trends of PCB concentrations in Lake Michigan coho and chinook salmon, 1975–2010

Abstract: The manufacture and use of polychlorinated biphenyls (PCBs) was banned in the United States in 1977 after it was determined that these compounds adversely affect animals and humans. The Wisconsin Department of Natural Resources has quantified total PCB concentrations in Lake Michigan chinook (n = 765) and coho (n = 393) salmon (Oncorhynchus tshawytscha and Oncorhynchus kisutch, respectively) filets since 1975. We analyzed these data to estimate trends in PCB concentrations in these fish . We used generalized l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 39 publications
0
18
1
Order By: Relevance
“…Lake Michigan Water Transfer Project (Chicago, USA) is one of the earliest and most controversial IBTs, since it has a long history of suffering from various kinds of contaminants such as persistent organic pollutants (Murphy and Rzeszutko 1977;Delfino, 1979;Rasmussen et al, 2014).…”
Section: Spread Of New Pollution and Diseasesmentioning
confidence: 99%
“…Lake Michigan Water Transfer Project (Chicago, USA) is one of the earliest and most controversial IBTs, since it has a long history of suffering from various kinds of contaminants such as persistent organic pollutants (Murphy and Rzeszutko 1977;Delfino, 1979;Rasmussen et al, 2014).…”
Section: Spread Of New Pollution and Diseasesmentioning
confidence: 99%
“…Wisconsin DNR data have also shown that PCB concentrations have decreased dramatically in Lake Michigan salmon species from 1975-2010, but the rate of decline is much less in recent years compared with the earliest years of data collected (Rasmussen et al, 2014). Similarly, longitudinal biomonitoring among a group of Great Lakes fish consumers has shown a decreased in serum PCBs over time, although the rate of decline was relatively slow at 3.5% per year (Knobeloch et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The global usage of PCBs culminated in the mid 1970's (Breivik et al, 2007), and since then concentrations in the environment have decreased dramatically (Schuster et al, 2010;Airaksinen et al, 2014;Pavlova et al, 2014;Rasmussen et al, 2014). Currently, the PCB decline in the environment is levelling off (Hansson et al, 2006;Thevenon et al, 2013;Airaksinen et al, 2014), which for the Baltic Sea also would imply stabilising PCB concentrations in biota.…”
Section: Introductionmentioning
confidence: 99%